The Role of Alcohol in the DNA Isolation Process: A Comprehensive Review - Sophian, Alfi (Poltekkes Kemenkes Kupang, 2025)
DNA isolation is a fundamental step in various molecular biology applications, with its success highly dependent on the purity and integrity of the isolated DNA. This review article aims to highlight the vital role of alcohol, particularly ethanol and isopropanol, in the DNA isolation process from various biological sources. This comprehensive review explores the biophysical principles underlying DNA precipitation by alcohol, where the reduction of the solution's dielectric constant and disruption of the hydration layer lead to DNA precipitation. The article also evaluates the application of alcohol in different DNA isolation protocols, including the classic phenol-chloroform extraction method, commercial silica column-based kits, and salting-out techniques. Recent advancements in optimizing alcohol precipitation parameters indicate that process efficiency can be enhanced by adjusting the type of alcohol, incubation time, and salt concentration. Current research trends also point toward the development of environmentally friendly approaches that minimize alcohol usage, as well as alternative alcohol-free methods such as magnetic-based technology and paper-based DNA isolation systems.The future prospects of DNA isolation are projected to integrate traditional alcohol-based methods with advanced technologies such as automation, nanomaterials, and microfluidic systems. A deeper understanding of alcohol’s role in DNA isolation is expected to optimize existing protocols and drive innovation in DNA isolation techniques for applications ranging from diagnostics to genomic research.